A quantitative assessment of the NCHRP 611 method for soil-structure interaction analysis of buried circular structures & a proposed improvement. (September 2019) - Zhang, W.; Esmaeilzadeh Seylabi, E.; Taciroglu, E.
Abstract: The recent National Cooperative Highway Research Program (NCHRP) Report 611 titled "Seismic Analysis and Design of Retaining Walls, Buried Structures, Slopes, and Embankments" has been widely adopted as a guideline in the analysis design of buried/embedded structures due to its computational simplicity and broadly accepted accuracy for simple soil-structure configurations. However, the method is not without shortcomings. In particular, the NCHRP method is not sensitive to the inherently broadband frequency content of seismic input excitations, soil heterogeneities, and potential kinematic interaction effects. The present study seeks to quantitatively assess the brackets of the validity of the NCHRP 611 method—specifically, for soil-structure analyses of buried circular structures, and offers an improvement that is simple to implement. This is achieved through parametric studies using detailed nonlinear finite element simulations involving a broad range of ground motions, and soil and structural properties. The simulations are carried out with models that are parametric variations of a model that has been validated in a prior centrifuge testing program on embedded structures. A refined version of the NCHRP 611 method, which uses maximum shear strains obtained through one-dimensional site response analyses, is shown to produce fairly accurate results for nearly all of the different cases considered in the parametric studies. The basic version of the method, however, which is based on rough estimates of maximum shear strain and effective soil modulus, is observed to be highly inaccurate.